Pengaruh Tingkat Pendidikan, Motivasi, Modal Usaha dan Karakteristik Wirausaha Terhadap Kinerja UMKM Sektor Kuliner di Kecamatan Buleleng - Ramdani, Nova Aulia; Sujana, I Nyoman (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This study aims to examine the effect of education level, motivation, business capital, and entrepreneurial characteristics on the performance of culinary sector MSMEs in the Buleleng Sub-district, both partially and simultaneously. The design of this study is causal quantitative. The population in this study was 168 MSMEs in the culinary sector with 63 respondents. The sample determination used a purposive sampling method. Data collection was carried out using the questionnaire distribution method. The data were analyzed using multiple linear regression analysis. The results of this study indicate that (1) there is a significant effect of education level; (2) there is a significant effect of motivation; (3) there is a significant effect of business capital; and (4) there is a significant effect of entrepreneurial characteristics on the performance of culinary sector MSMEs in Buleleng District, both partially and simultaneously.